Peritoneal hydatus. Heterotopic vesicle - Bortagaray, Carlos; Errandonea, Jorge; Rodríguez Arraras, Nelson; Villar, Ariel (Cirugía del Uruguay, 1973)
Case material consists of two patients suffering from hydatid cyst with heterotopic vesicle in peritoneum: one of them with hyaline content and the other supurated and treated through surgery 23 days after parturition. An insheathment membrane was found covering the visceral plane and preventing view of rupture of primitive cyst. No similar Óbservation has been found in national bibliography.